Dispersal limitation determines large‐scale dark diversity in Central and Northern Europe. (24th April 2017) - Riibak, Kersti; Ronk, Argo; Kattge, Jens; Pärtel, Meelis
Abstract: Aim: Previous studies indicate that many plant species present in a surrounding region are absent from potentially suitable sites (i.e. they constitute dark diversity). However, quantitative analyses are lacking where and why dispersal limitation occurs within species occurrence range at the continental scale. We test if species characteristics related to dispersal limitation, that is, low seed production and short potential dispersal distance, affect the formation of dark diversity at large spatial scales. In addition, we explore how the levels of dispersal limitation are affected by climate, landscape heterogeneity and anthropogenic activity. Location: Seven study areas in Central and Northern Europe – Iceland, Finland, Estonia, the British Isles, the Netherlands, Germany and Switzerland. Methods: We used data on vascular plant species occurrences in ca. 10 × 10 km grid cells from each study area. To estimate dark diversity for each grid cell, we applied geographical, biogeographical and environmental filters. Seed production was estimated directly (number of seeds per ramet), and indirectly from seed mass. We used several plant traits in combination (e.g. dispersal syndrome and seed characteristics) to estimate potential dispersal distance of seeds. Results: Species contributing to dark diversity produced generally fewer seeds and had shorter potential dispersal distances than observed species. Dispersal limitation tended to decrease with increasing environmental stress, human population density and agricultural land use. Main conclusions: Many species are absent from potentially suitable sites in Central and Northern Europe because of dispersal limitation, induced by low seed production and short potential dispersal distances. However, strong abiotic stress, biotic resistance and human activities have reduced the importance of dispersal limitation. This knowledge can be considered in the predictions of how changes in climate and land use affect biodiversity in the future.